2020
DOI: 10.3390/biom10121690
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative View on the Oviductal Environment during the Periconception Period

Abstract: The oviduct plays important roles in reproductive events: sperm reservoir formation, final gamete maturation, fertilization and early embryo development. It is well known that the oviductal environment affects gametes and embryos and, ultimately, the health of offspring, so that in vivo embryos are better in terms of morphology, cryotolerance, pregnancy rates or epigenetic profile than those obtained in vitro. The deciphering of embryo–maternal interaction in the oviduct may provide a better understanding of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 211 publications
(300 reference statements)
1
11
0
Order By: Relevance
“…In porcine, the addition of oviductal EVs to the IVF medium regulates polyspermy [ 68 ], while oviductal EVs isolated from oviductal fluid improve bovine embryo quality during in vitro culture, in terms of blastocyst rates, cell number, hatching rates, embryo cryosurvival and gene expression [ 69 ]. It has been demonstrated that the molecular composition of oviductal EVs is regulated by steroid hormones [ 70 ] and that the OVGP1-protein is contained in the oviductal EVs (see [ 71 ] for references).…”
Section: Discussionmentioning
confidence: 99%
“…In porcine, the addition of oviductal EVs to the IVF medium regulates polyspermy [ 68 ], while oviductal EVs isolated from oviductal fluid improve bovine embryo quality during in vitro culture, in terms of blastocyst rates, cell number, hatching rates, embryo cryosurvival and gene expression [ 69 ]. It has been demonstrated that the molecular composition of oviductal EVs is regulated by steroid hormones [ 70 ] and that the OVGP1-protein is contained in the oviductal EVs (see [ 71 ] for references).…”
Section: Discussionmentioning
confidence: 99%
“…In the oviduct, a large number of secretory epithelial cells provide essential environmental and nutritional support for early embryonic development (Li & Winuthayanon, 2017). Oviduct epithelial cells (OESs) secrete oviductal fluid (OF) and play important roles in reproductive events, participating in final gamete maturation, fertilization, and early embryonic development (González‐Brusi et al, 2020; Tukur et al, 2020). Moreover, the OF mediates an early embryo‐maternal dialog through cell‐to‐cell contacts, secreted molecules, and extracellular vesicles (EVs) (Lee et al, 2021; Saint‐Dizier, Schoen, Chen, Banliat, & Mermillod, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Among oviductal factors identified in the oviductal fluid, OVGP1 has been well characterized and suggested to play important roles in the process of several mammalian species, including humans [for review, see Araki & Yoshida-Komiya, 1998; Buhi 2002; Avilés et al, 2010; González-Brusi et al, 2020; Zhao et al, 2022]. Using the golden hamster as a model, which has provided a wealth of knowledge concerning the mammalian reproductive process [Hirose & Ogura, 2019], Ovgp1 -knockout (KO) animals were generated using gene editing technology (Suppl.…”
Section: Resultsmentioning
confidence: 99%